Using an arts‐based approach to explore the building of social capital at a therapeutic recreation camp. (27th April 2021) - Jay, Elissa‐Kate; Moxham, Lorna; Patterson, Christopher
Abstract: Therapeutic recreation is beneficial for people with and without disabilities, promoting an empowered, connected, and joyful life. The present study aimed to analyse canvas art created on a therapeutic recreation programme called  Recovery Camp, to discover what they reveal about the shared experiences which have occurred. This study utilized an arts‐based research method and thematic analysis to discover what participants have communicated via their artwork from ten camps between 2018 and 2019. This study adheres to the COREQ guidelines for qualitative studies. Reflexive thematic analysis produced subthemes which informed three main themes and an identified core meaning of  Social Capital . The three main themes were Togetherness and teamwork,   Positivity, and  Gratitude for Recovery Camp . Based on these findings, canvas art has revealed that shared experiences during a therapeutic recreation camp were positive and connecting. Social capital was created and bridged at Recovery Camp  through teamwork and prosocial attitudes. Gratitude has also been disclosed by participants for their shared positive experience.